A miRNA-based signature detected in primary melanoma tissue predicts development of brain metastasis - Hanniford, Doug (Clin Cancer Res, 2015)
PURPOSE: Brain metastasis is the major cause of mortality among melanoma patients. A molecular prognostic test that can reliably stratify patients at initial melanoma diagnosis by risk of developing brain metastasis may inform the clinical management of these patients. EXPERIMENTAL DESIGN: We performed a retrospective, cohort-based study analyzing genome-wide and targeted microRNA expression profiling of primary melanoma tumors of three patient cohorts (n= 92, n= 119, n= 45) with extensive clinical follow up. We used Cox regression analysis to establish a microRNA-based signature that improves the ability of the current clinicopathologic staging system to predict the development of brain metastasis. RESULTS: Our analyses identified a 4-microRNA (miR-150–5p, miR-15b-5p, miR-16–5p, and miR-374b-3p) prognostic signature that, in combination with stage, distinguished primary melanomas that metastasized to the brain from non-recurrent and non-brain-metastatic primary tumors (training cohort: C-index=81.4%, validation cohort: C-index=67.4%, independent cohort: C-index=76.9%). Corresponding Kaplan-Meier curves of high- vs. low-risk patients displayed a clear separation in brain-metastasis-free and overall survival (training: p<0.001, p<0.001, validation: p=0.033, p=0.007, independent: p=0.021, p=0.022, respectively). Finally, of the microRNA in the prognostic model, we found that the expression of a key lymphocyte miRNA, miR-150–5p, which is less abundant in primary melanomas metastatic to brain, correlated with presence of CD45(+) tumor infiltrating lymphocytes. CONCLUSIONS: A prognostic assay based on the described miRNA expression signature combined with the currently used staging criteria may improve accuracy of primary melanoma patient prognoses and aid clinical management of patients, including selection for adjuvant treatment or clinical trials of adjuvant therapies.